"EFEKTIVITAS KEGIATAN PROMOSI TERHADAP KEPUTUSAN PILIHAN PROGRAM STUDI ( STUDI KASUS MAHASISWA PROGRAM STUDI MANAJEMEN UNWIKU ): "EFEKTIVITAS KEGIATAN PROMOSI TERHADAP KEPUTUSAN PILIHAN PROGRAM STUDI ( STUDI KASUS MAHASISWA PROGRAM STUDI MANAJEMEN UNWIKU ) - Ratna Pujiastuti Ratna; Herwiek Diyah Lestari (Majalah Imiah Manajemen & Bisnis, 2021)
This Article, entitled The Effectiveness of Promotion Mix Against the decision of choice of study programs, by taking respondents from students majoring in Management, Faculty of Economics and Business. This research is motivated by the author's desire to examine the Promotion Activity Factors that are most effective in choosing a Study Program, especially in the Management Study Program of the University of Wijayakusuma Purwokerto. The proposed hypothesis is: Advertising, visits, WEB, Alumni have a significant influence on the student's decision to choose a study program Management. The analytical tool used is multiple linear regression. Based on the calculation of the F test and the t test it is known that the value of F count is greater than F Table, t count for X1 and X4 is greater than t table. This means that both advertising, alumni have a significant influence on student decisions in choosing a study program in management, but for X2 and X3 t count is smaller than t table. So visits and the Web do not have a significant effect on student the decision choices in the Management study program. The implication of this research is that the Management Study Program really needs to pay more attention to advertisements and the use of Alumni to increase the interest of prospective students in choosing study programs. This advertisement is carried out by showing more or using local television media, while the use of alumni channels can be increased cooperation in order to create a more harmonious relationship. For the Web, it is recommended that it be more varied. Meanwhile, the personnel can better prepare visits to SMA / SMK by including training in effective communication about doing business.